2021
DOI: 10.1002/adfm.202106958
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Nature: Constructing a Smart Bionic Structure for High‐Performance Glucose Sensing in Human Serums

Abstract: Traditional noble metal-based catalysts for glucose sensing usually suffer from easy deactivation by halides and weak sensing properties. To unravel these limits, herein, a novel nature-inspired design concept (mimicking a "rock-soil-grass" geotexture system) is purposed to build a free-standing hierarchical micro-nano architecture. Thanks to the design (rigid and conductive Ni foam) ("rock", underlayer, rough and highly disordered graphene nanosheets (GNSs) ("soil", middle-layer), and strong catalytic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Oliver et al reported that the Cu 2 O template could be spontaneously etched during the synthetic procedure to react with the added tricarboxylic acid (BTC) and tetrabutylammonium tetrauoroborate to form HKUST-1 MOF lms. 28 Inspired by the intelligent natural geotexture of forests predominantly composed of trees established through planting and/or seeding in the soil covered on the underground rock, and their fascinating synergistic effects in ion transport, 29 herein, we demonstrate an effective strategy to construct three-dimensional (3D) ZnO@zeolitic imidazolate framework-8 (ZIF-8)-derived ZnO@Ni/Co-LDH lms for high-performance EC energy storage devices for the rst time. Glass substrates coated with transparent and electrically conducting layers of uorine doped tin oxide (FTO) were used to simulate the soil-rock structure to supply abundant growth sites and adhesive force for active materials to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Oliver et al reported that the Cu 2 O template could be spontaneously etched during the synthetic procedure to react with the added tricarboxylic acid (BTC) and tetrabutylammonium tetrauoroborate to form HKUST-1 MOF lms. 28 Inspired by the intelligent natural geotexture of forests predominantly composed of trees established through planting and/or seeding in the soil covered on the underground rock, and their fascinating synergistic effects in ion transport, 29 herein, we demonstrate an effective strategy to construct three-dimensional (3D) ZnO@zeolitic imidazolate framework-8 (ZIF-8)-derived ZnO@Ni/Co-LDH lms for high-performance EC energy storage devices for the rst time. Glass substrates coated with transparent and electrically conducting layers of uorine doped tin oxide (FTO) were used to simulate the soil-rock structure to supply abundant growth sites and adhesive force for active materials to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…3 What is more, diabetes can induce a variety of chronic complications, such as blindness, coronary heart disease, kidney failure, and others. 1,4,5 Therefore, scientists paid increasing attention to developing accurate, rapid, and reliable measurements of blood glucose for clinical diagnosis and biomedical application.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 However, the high cost or complex immobilization techniques limit their development. 5 In contrast, inorganic catalysts can electro- catalyze glucose directly on nonenzymatic surfaces, so the nonenzyme sensor can be reused and stored for a long time. 15 Thus, more and more reports discussed the research of nonenzymatic sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations